Clinical efficacy and effect on neurotransmitter levels of Shaoma Zhijing granules in children with tic disorders - Wang, Yanping; Jing, Miao; Hua, Ying; Zhang, Lin; Wang, Jianbiao; Fan, Xiaochun (Frontiers in Pediatrics, 2025)
ObjectiveTo investigate the clinical efficacy of Shaoma Zhijing Granules in treating pediatric tic disorders and its impact on plasma neurotransmitter levels.MethodsEighty pediatric patients with tic disorders were randomly divided into the Shaoma Zhijing group (40 cases) and the Tiapride group (40 cases). The Yale Global Tic Severity Scale (YGTSS) scores, clinical efficacy, and traditional Chinese medicine (TCM) syndrome evaluations were compared at baseline, 4 weeks, and 8 weeks after treatment. Ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) was used to analyze the changes in plasma neurotransmitter levels before and after treatment.ResultsCompared with baseline, both groups showed a decrease in YGTSS scores and TCM syndrome scores at 4 weeks and 8 weeks after treatment (P < 0.05). No statistically significant differences were observed between the two groups (P > 0.05). The effective rates were 90% for the Shaoma Zhijing group and 80% for the Tiapride group, with the incidence of adverse reactions being 2.5% and 15%, respectively. After 8 weeks, serum levels of glutamic acid (Glu), aspartic acid (Asp), dopamine (DA), norepinephrine (NE), and epinephrine (E) in both groups were significantly lower than baseline (P < 0.05), while gamma-aminobutyric acid (GABA) levels were significantly higher (P < 0.05). Significant differences were also observed between the two groups in DA, NE, E, and GABA levels after treatment (P < 0.05).ConclusionShaoma Zhijing Granules demonstrate significant clinical efficacy and good safety in treating pediatric tic disorders. They effectively improve symptoms, thereby contributing to the enrichment of the TCM diagnostic and treatment system for pediatric tic disorders.